Kawasaki Disease Associated Acute Abdomen: Most Require No Surgery - She X; Chen J; Zhou YN; Guo J; Zhao FH; Yi C (Dove Medical Press, 2023)
Xiang She, Jia Chen, Yu-Neng Zhou, Jun Guo, Feng-Hua Zhao, Cong Yi Department of Pediatrics, Mianyang Central Hospital, School of Medicine, University of Electronic Science and Technology of China, Mianyang, 621000, People's Republic of ChinaCorrespondence: Cong Yi, Department of Pediatrics, Mianyang Central Hospital, School of Medicine, University of Electronic Science and Technology of China, Mianyang, 621000, People's Republic of China, Email congyi6649@126.comObjective: To summarize the clinical features and treatment experiences of patients with Kawasaki disease (KD)-associated acute abdomen (KD-AA).Methods: We conducted a retrospective case-control study of patients with KD-AA treated at our hospital between January 2006 and November 2022.Results: Of the 917 children with KD, 43 (4.7%) presented with AA. Of these, 33 with complete information were included in the KD-AA group. Patients with KD-AA were significantly older, with higher neutrophil rate, C‐reactive protein, procalcitonin, and alanine transaminase levels and lower hemoglobin, albumin, and serum sodium levels. Additionally, more patients with KD-AA presented with aseptic meningitis and KD shock syndrome than those with KD alone (all p< 0.05). The two groups did not differ in the incidence of intravenous immunoglobulin (IVIG) resistance, incomplete KD, or coronary artery abnormalities. All patients received aspirin and IVIG therapy, with nine receiving a second dose of IVIG and 11 receiving corticosteroids. Only two patients with KD-AA underwent surgery, and the prognosis of all patients with KD-AA was good.Conclusion: KD-AA should be suspected in febrile children with abdominal symptoms. Prompt diagnosis of KD-AA is important for early effective treatment to avoid unnecessary surgical harm. KD, complicated by acute abdomen, has a good prognosis.Keywords: Kawasaki disease, acute abdomen, clinical manifestation, treatment